2019
DOI: 10.1093/neuros/nyz103
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Percutaneous Balloon Compression, Thermocoagulation, and Glycerol Rhizolysis for Trigeminal Neuralgia in Multiple Sclerosis

Abstract: BACKGROUND Balloon compression (BC), thermocoagulation (TC), and glycerol rhizolysis (GR) are percutaneous surgical options for trigeminal neuralgia (TN). Whether the outcomes of these procedures in multiple sclerosis -related TN (MS-TN) are as effective as in idiopathic TN (ITN) is unknown. OBJECTIVE To retrospectively compare pain relief, complications, and durability achieved by these 3 types of procedures in MS-TN and ITN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Structural abnormalities in the myelin sheath (1) can lead to a variety of neurological conditions (25), such as Alzheimer’s disease (6), Pelizaeus-Merzbacher disease (7), multiple sclerosis (8), experimental allergic encephalomyelitis (9), and pathological neuropathic pain (10). The morphology of the myelin sheath differs slightly among the brain, spinal cord, and peripheral nerves, but all have an axon that is concentrically wrapped by glial cells, with the myelin sheath formed on the outer surface of the axon.…”
mentioning
confidence: 99%
“…Structural abnormalities in the myelin sheath (1) can lead to a variety of neurological conditions (25), such as Alzheimer’s disease (6), Pelizaeus-Merzbacher disease (7), multiple sclerosis (8), experimental allergic encephalomyelitis (9), and pathological neuropathic pain (10). The morphology of the myelin sheath differs slightly among the brain, spinal cord, and peripheral nerves, but all have an axon that is concentrically wrapped by glial cells, with the myelin sheath formed on the outer surface of the axon.…”
mentioning
confidence: 99%
“…Except PBC, other microinvasive approaches, such as gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, were also reported to be useful in treatment of ITN [1,[6][7][8][9]. A recently published meta-analysis concerning TN showed that glycerol rhizotomy showed similar rate of immediate pain relief and pain recurrence with PBC but showed lower incidences of numbness and diplopia, while the incidences of other complications were similar in both groups [9].…”
Section: Discussionmentioning
confidence: 99%
“…Different from other subgroups where neurovascular compression or underlying diseases can easily be identified, ITN does not show significant abnormalities in electrophysiological tests or MRI scans, which makes etiological targeted surgeries impossible [5]. Other surgeries, such as percutaneous balloon compression (PBC), gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, have repeatedly been reported to be useful for pain control in TN for which pharmacological treatments have failed [1,[6][7][8][9]. Among these surgical options, PBC is a commonly used microinvasive technique and shows potential in the control of TN [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Ten patients who had an MVD were lost to follow-up; 1 patient with a percutaneous procedure (TC) was lost to follow-up ( P = 0.055, 2-sided Fisher’s exact test). Cases with MS or repeat surgery have been reported separately [ 34 , 35 ]. All patients in this work had typical (Burchiel type I [ 8 ]) TN pain, meeting the criteria of pain in the distribution of the trigeminal nerve (Vn); an intermittent, paroxysmal course; shock-like lancinating character; light-touch triggers; and initial response to TN medications.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term relief rates for MVD have been reported to range between 70 and 80% at 5–10 years in several large series [ 4 , 42 , 52 ]. The relief rates for percutaneous surgery for TN are more variable and influenced by surgical technique and patient factors [ 6 , 20 , 28 , 44 , 46 , 34 , 35 ]. Comparing between studies is often challenging owing to the heterogeneity in outcome measures employed.…”
Section: Introductionmentioning
confidence: 99%